Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/1103308817743371
|View full text |Cite
|
Sign up to set email alerts
|

Positivity Ratio Links Self-control Skills to Physical Aggression and Happiness in Young Palestinians Living in Gaza

Abstract: The study examined a potential underlying mechanism through which self-control skills (SCSs) may predict more happiness on the one hand and less hostility, anger and peer aggression on the other hand in an understudied sample of 744 Palestinian youngsters (Grades 8-12) from the Gaza Strip, a military conflict area. The hypothesized model was confirmed: self-reported SCS linked with happiness through positivity ratio as a mediator; SCS linked with physical aggression through the association of positivity ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…With respect to SC skills, we expected female adolescents to report on higher SC skills in comparison with male adolescents (Hypothesis 2). The findings corroborate previous studies (e.g., Brody & Hall, 2010; Nolen-Hoeksema, 2012; Orkibi & Ronen, 2017; Ronen et al, 2013; Rosenbaum, Ronen, Abuelaish, Orkibi, & Hamama, 2018) that report higher SC skill scores in females versus males. A plausible explanation might be related to the developmental changes occurring in adolescence in terms of brain development, endocrinology, emotions, cognition, behavior, and interpersonal relationships (Goldbeck, Schmitz, Nesier, Herschbach, & Henrich, 2007; Žukauskienė, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…With respect to SC skills, we expected female adolescents to report on higher SC skills in comparison with male adolescents (Hypothesis 2). The findings corroborate previous studies (e.g., Brody & Hall, 2010; Nolen-Hoeksema, 2012; Orkibi & Ronen, 2017; Ronen et al, 2013; Rosenbaum, Ronen, Abuelaish, Orkibi, & Hamama, 2018) that report higher SC skill scores in females versus males. A plausible explanation might be related to the developmental changes occurring in adolescence in terms of brain development, endocrinology, emotions, cognition, behavior, and interpersonal relationships (Goldbeck, Schmitz, Nesier, Herschbach, & Henrich, 2007; Žukauskienė, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…The female students' self‐control and problem‐solving skills were found to be significantly higher than those of the male students. Concurring with the findings of the present study, recent studies in the literature have reported self‐control and problem‐solving skills to be significantly higher in women than in men 3,8,18,24,25 . In Yakut's 6 study of self‐control among university students, although the self‐control scores of female students were higher than those of their male counterparts, the difference was not found to be statistically significant.…”
Section: Discussionsupporting
confidence: 74%
“…2,4 High self-regulation ensures individuals take responsibility for their behaviors. 24 One's ability to cope with an encountered problems is closely related to one's level of selfcontrol. 6 Although self-control and problem-solving skills are considered important for everyone, they are even more important for undergraduate nursing students, given their role in providing healthcare In the study, it was investigated whether the scale scores were affected by the respondents' gender, social class, longest place residence, smoking status, economic status, and family type.…”
Section: The Relationship Between Nursing Students' Self-control and ...mentioning
confidence: 99%
“…If problems, obstacles or situations of self-conflict are encouraged, Bandura's self-control theory believes that a suitable behaviour or ability will be selected to reach the expected goals. Later, Rosenbaum (1980) and Rosenbaum et al (2018) modified and further expanded the characteristics of individual self-regulation as follows.…”
Section: Validation Of Employees' Self-leadershipmentioning
confidence: 99%